Extracts of feverfew inhibit mitogen-induced human peripheral blood mononuclear cell proliferation and cytokine mediated responses: a cytotoxic effect - O'NEILL, LUKE ANTHONY JOHN (British Pharmacological Society, 1987)
Feverfew has been used since antiquity to treat inflammatory conditions. Extracts of the herb were found to inhibit mitogen-induced tritiated thymidine ([3H]-TdR) uptake by human peripheral blood mononuclear cells (PBMC), interleukin 2 (IL-2)-induced [3H]-TdR uptake by lymphoblasts and PGE2 release by interleukin 1 (IL-1)-stimulated synovial cells. Parthenolide, a major secondary metabolite from the herb also blocked [3H]-TdR uptake by mitogen-induced PBMC. However, both crude extracts and parthenolide proved cytotoxic to mitogen-induced PBMC and IL-1 stimulated synovial cells, the cytotoxic effect being functionally indistinguishable from the inhibitory effects. The pharmacological properties of feverfew may thus be due to cytotoxicity, although the time course of the events described in this paper is different from those where feverfew appears to have more specific inhibitory effects.
PUBLISHED
Keywords: feverfew rheumatoid arthritis cytokines